How coaching works : the essential guide to the history and practice of effective coaching - O'Connor, Joseph, 1948 September 12-; Lages, Andrea (London : A. & C. Black, 2007)
This book draws together the key themes and principles of coaching, revealing the ideas that work at the root of all successful coaching techniques. It is a must-have for practising coaches, students and anyone interested in this increasingly popular subject.
Coaching on the Edge of Chaos -- The History of Coaching: The People -- The History of Coaching: The Times -- Coaching in Europe and the United States: The Inner Game, GROW and Coactive Coaching -- Integral Coaching -- NLP Coaching -- Positive Psychology Coaching -- Behavioural Coaching -- Ontological Coaching: Interview with Fernando Flores -- An Integrated Mode -- Measuring the Results of Coaching -- Developmental Coaching -- Post-modern Coaching.
Includes bibliographical references (pages 263-266) and index.
Print version record.
Keywords: Personal coaching; Personal coaching -- History; Self-help & personal development; Business communication & presentation; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Personal coaching; Coaching; Coaching; Electronic books; History